The Effect of Lighting Program and Melatonin on the Alleviation of the Negative Impact of Heat Stress on the Immune Response in Broiler Chickens - Abbas, Ahmed O.; Gehad, Ahmed E.; Hendricks, Gilbert L.; Gharib, H.B.A.; Mashaly, Magdi M. (International Journal of Poultry Science, 2007)
Two experiments were conducted to study the effect of lighting program and melatonin addition to the diet on the immune responses of broiler chickens under chronic heat stress. In the first experiment, two groups of male broiler chickens received Continuous Light (CL) (23L: 1D) while another two groups received Intermittent Light (IL) (1L: 3D). From 4 to 6 wk of age, a group from each light program was exposed to 35 °C versus 24 °C for the other two groups. Heat stressed chickens under IL had significantly lower (p<0.05) body temperatures, pro-inflammatory cytokines levels and corticosterone concentrations in their plasma, compared to the heat stressed chickens under CL. Furthermore, in the heat stressed groups, the IL group had a significantly higher (p<0.05) cutaneous basophil hypersensitivity response and T-cell proliferation, compared to the CL group. In the second experiment, two groups of male broiler chickens were fed a diet containing melatonin (40 ppm), while the other two groups received a melatonin free diet (0 ppm), from 4 to 6 wk of age. Concurrently, a group from each melatonin treatment was exposed to 35 °C versus 24 °C in the other group. The heat stressed chickens receiving melatonin had significantly lower (p<0.05) body temperatures, pro-inflammatory cytokines IL-1 and IL-6 and corticosterone concentrations. Furthermore, in the heat stressed birds, the melatonin group had a higher but not significant cutaneous basophil hypersensitivity response and T-cell proliferation. The current study indicates that intermittent light and melatonin administration can be used to ameliorate immunosuppression associated with heat stress in broiler chickens.